LA BÚSQUEDA DE EFECTOS HUMORÍSTICOS, IRÓNICOS Y PARÓDICOS A TRAVÉS DE LOS ANGLICISMOS - Rodríguez Medina, María Jesús (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Many studies have dealt with anglicisms in Spanish since it became a noticeable linguistic phenomenon at the end of the 1960s. In the beginning, most books and articles focused on analysing anglicisms used to designate new objects and concepts, or criticising those regarded as ‘useless intruders’ by linguists with a purist approach. Forty years later this purist tradition no longer exists and new aspects of anglicisms such as their presence in syntax or their expressive uses have attracted the attention of scholars. In this paper, we analyse a corpus of anglicisms and pseudoanglicisms found in television and radio humorous programmes in Spain where they are exploited in expressive comic messages to catch the public’s eye.